Epidemiology of atrial fibrillation - Zatloukalová, Anna (Profese Online, 2020)
Background: Atrial fibrillation is a pending rhythm disorder in the population. Its incidence and prevalence are increasing not only in the Czech Republic but also in the world. It is therefore possible that it threatens to  trust.Objective: The aim of the communication is to acquaint healthcare professionals across this field with this topic.Methods: A search method was used to find available words in Czech, but especially in foreign databases.Results: In the Czech Republic there are almost 300,000 patients, in the world the number is climbing to 30  million patients and is growing every year. Age, gender, and genetic factors are not controllable risk factors. Other risk factors include obesity, metabolic syndrome, chronic kidney disease or hypertension. Warfarin is  often used in therapy of atrial fibrillation. New direct oral anticogulants are currently available: dabgatran, rivaroxaban, apixaban and darexban.Conclusions: Fibrillation-causing illnesses, initial numbers, as your life span increases, increase your year. Many risk factors for atrial fibrillation are preventable. It is therefore appropriate to focus on the prevention of, in particular, lifestyle risk factors.
Keywords: epidemiology; atrial fibrilation; risk factors; prevention